2006
DOI: 10.1126/science.1124513
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Receptor Specificity of the Hemagglutinin from an H5N1 Influenza Virus

Abstract: The hemagglutinin (HA) structure at 2.9 angstrom resolution, from a highly pathogenic Vietnamese H5N1 influenza virus, is more related to the 1918 and other human H1 HAs than to a 1997 duck H5 HA. Glycan microarray analysis of this Viet04 HA reveals an avian a2-3 sialic acid receptor binding preference. Introduction of mutations that can convert H1 serotype HAs to human a2-6 receptor specificity only enhanced or reduced affinity for avian-type receptors. However, mutations that can convert avian H2 and H3 HAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
847
1
7

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 884 publications
(887 citation statements)
references
References 47 publications
32
847
1
7
Order By: Relevance
“…This finding demonstrated that the isolates with avian specific receptor binding properties can replicate and cause infection in equines. Different amino-acids that are implicated in receptor specificity Y98, S136, W153, H183, E190, K193 L194 E216 P221 K222 G225, Q226, S227, G228 (H3 influenza numbering) were tested [26]. Interestingly 98 (Y to N), 193 (K to R), 216 (E to K) and 221(P to S) which were found in the examined equine isolate have also been in many other isolates from the middle east in the flu database which raises a question as to what the impact of such substitution on HA binding to human receptors is.…”
Section: Resultsmentioning
confidence: 99%
“…This finding demonstrated that the isolates with avian specific receptor binding properties can replicate and cause infection in equines. Different amino-acids that are implicated in receptor specificity Y98, S136, W153, H183, E190, K193 L194 E216 P221 K222 G225, Q226, S227, G228 (H3 influenza numbering) were tested [26]. Interestingly 98 (Y to N), 193 (K to R), 216 (E to K) and 221(P to S) which were found in the examined equine isolate have also been in many other isolates from the middle east in the flu database which raises a question as to what the impact of such substitution on HA binding to human receptors is.…”
Section: Resultsmentioning
confidence: 99%
“…The soluble 09H1 (A/California/04/2009) was prepared based on the method described by Stevens et al in a baculovirus expression system (Stevens et al, , 2006Ekiert et al, 2009). The construct incorporated a C-terminal thrombin cleavage site, a trimerizing sequence ('foldon') and a hexa His-tag at the extreme C terminus of the construct to enable protein purification.…”
Section: Resultsmentioning
confidence: 99%
“…[11] Considering that glycans are ubiquitous biomolecules, which, in many cases, are key to protein function, [12][13][14] it is evident that glycans are useful means for addressing various questions in the fields of basic and applied research, relating to the areas of biomimetics, drug targeting, vaccine design, [15] or diagnostics. [16,17] Vital cellular functions that are regulated or influenced by glycans include, for instance, recognition, signaling, trafficking, biological half life, and adhesion events; several immunological phenomena are also enabled and enhanced through glycan "signals" on proteins. Thus, engineering of tailor-made ("functional") glycoproteins (neoglycoproteins) will decisively change our capability to influence and control complex biological systems.…”
Section: Introductionmentioning
confidence: 99%